An in silico parametric model of vertebrae trabecular bone based on density and microstructural parameters to assess risk of fracture in osteoporosis. (December 2014) - Amjadi Kashani, Mohammad Reza; Nikkhoo, Mohammad; Khalaf, Kinda; Firoozbakhsh, Keikhosrow; Arjmand, Navid; Razmjoo, Arash; Parnianpour, Mohamad
Osteoporosis is a progressive bone disease characterized by deterioration in the quantity and quality of bone, leading to inferior mechanical properties and an increased risk of fracture. Current assessment of osteoporosis is typically based on bone densitometry tools such as Quantitative Computed Tomography (QCT) and Dual Energy X-ray absorptiometry (DEXA). These assessment modalities mainly rely on estimating the bone mineral density (BMD). Hence present densitometry tools describe only the deterioration of the quantity of bone associated with the disease and not the affected morphology or microstructural changes, resulting in potential incomplete assessment, many undetected patients, and unexplained fractures. In this study, an in-silico parametric model of vertebral trabecular bone incorporating both material and microstructural parameters was developed towards the accurate assessment of osteoporosis and the consequent risk of bone fracture. The model confirms that the mechanical properties such as strength and stiffness of vertebral trabecular tissue are highly influenced by material properties as well as morphology characteristics such as connectivity, which reflects the quality of connected inter-trabecular parts. The FE cellular solid model presented here provides a holistic approach that incorporates both material and microstructural elements associated with the degenerative process, and hence has the potential to provide clinical practitioners and researchers with more accurate assessment method for the degenerative changes leading to inferior mechanical properties and increased fracture risk associated with age and/or disease such as Osteoporosis.